(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
A retrospective cross-sectional study was conducted with the inclusion of women with preeclampsia. The perinatal outcome was assessed in newborns born after the 28th week of pregnancy and during the early neonatal period before discharge (< 7 days). The aim of the study was to evaluate the effect of preeclampsia treatment methods on perinatal outcomes. Perinatal mortality was high among women in labor with preeclampsia. According to our analysis, the most pronounced negative impact on perinatal outcomes is exerted by such variables as diastolic blood pressure and an Apgar score at the 5th minute.